Improving Students' Speaking Competence By Using Games For The Second Grade Students Of Sma Al Islam 1 Surakarta Academic Year 2008/2009 - Hartati, Sih Minarsi (2012)
his research aims at observing the implementation of language games teaching technique to the teaching of English Speaking at SMA Al Islam 1 Surakarta and its affect upon students' learning. The research was conducted at the second grade students of SMA Al Islam 1 Surakarta 2008/ 2009 academic year. In this research, the problem refers to the second grade students in learning English especially their speaking competence which is still low. Related to the above problem, the writer thinks that language games technique is the most appropriate one that can be used to increase their ability and motivation to study English especially English Speaking. The research was a classroom action research. The research methodology included setting and time of the research, the subject of the research, the method of the research, the procedure of the research and technique of collecting data. The writer divided the action into three cycles and carried out in four steps namely action plan, action implementation, observation, and reflection. The cycles were determined at the time of implementation in which after looking at the result of the first cycle, then followed by the next cycles to see the consistency of the significant data. The result of the implementation showed that the use of language games improved and enhanced the students' English speaking competence. It could be seen from their ability and the results increased. Their main obstacles are like shy, nervous, afraid to make mistakes, and even inferior significantly decreased. Besides, from the collected data, the students had better progress from cycle one to the next cycle. For instance, the mean of pre - test was 58.16, while the mean of cycle one was 61.13, cycle two was 65.62, and cycle three was 70.2. Based on the above result, it could be concluded that the use of language games technique really improved the students' achievement in learning English especially in English speaking. The improvement was quite significant which was reflected from the progress of students' score from one cycle to another, besides their increasing motivation, self confident and interest. iv Related to the research findings above, the writer wanted to propose some suggestions for the English teacher in the secondary school, especially at SMA Al Islam 1 Surakarta as follows: Firstly, explanation the most appropriate technique before conducting the teaching and learning process in the class. Secondly, creation the most appropriate approach to make the students not to be shy, nervous, and afraid to make mistakes, or even feel inferior to communicate with others in English. The last, create an interesting and enjoyable atmosphere during the class activity in order to make the students easier and more bravery to express their own English orally. The researcher finding implies that language games can be alternative technique to promote students' speaking skill and it is for the other researcher to develop the aspect of speaking skill which has not been developed in the research. Language games is the best effect is on the active participation during the speaking class.